2015
DOI: 10.5713/ajas.14.0860
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nucleotide Variations, Haplotypes Structure and Associations with Growth Related Traits of Goat AT Motif-Binding Factor (<i>ATBF1</i>) Gene

Abstract: The AT motif-binding factor (ATBF1) not only interacts with protein inhibitor of activated signal transducer and activator of transcription 3 (STAT3) (PIAS3) to suppress STAT3 signaling regulating embryo early development and cell differentiation, but is required for early activation of the pituitary specific transcription factor 1 (Pit1) gene (also known as POU1F1) critically affecting mammalian growth and development. The goal of this study was to detect novel nucleotide variations and haplotypes structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…These studies showed that the ATBF1 gene was hypothesized to produce important effects on cell differentiation and early development, suggesting that the ATBF1 gene would affect the growth traits in animals. In our team, Zhang et al (2015) first explored the single nucleotide polymorphisms (SNPs) and haplotype structure of the goat ATBF1 gene and analyzed its associa- tions with growth-related traits in two Chinese goat breeds. Xu et al (2017) identified crucial SNP variations within the ATBF1 gene in native Chinese cattle breeds.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that the ATBF1 gene was hypothesized to produce important effects on cell differentiation and early development, suggesting that the ATBF1 gene would affect the growth traits in animals. In our team, Zhang et al (2015) first explored the single nucleotide polymorphisms (SNPs) and haplotype structure of the goat ATBF1 gene and analyzed its associa- tions with growth-related traits in two Chinese goat breeds. Xu et al (2017) identified crucial SNP variations within the ATBF1 gene in native Chinese cattle breeds.…”
Section: Introductionmentioning
confidence: 99%
“…However, in SBWC goats, the frequency of the "D" allele was lower than that of the previous study, which could be due to the sample sizes in this experiment being smaller. Furthermore, no breed was in accordance with the HWE, suggesting that the populations of the three breeds were not in dynamic equilibrium, due to migration, genetic drift, and artificial selection [43]. Overall, this polymorphic mutation had a high frequency and was present in all three goat breeds from different regions, indicating that this polymorphic mutation is genetically stable in goats and shows potential as a candidate DNA marker in molecular breeding progress.…”
Section: Discussionmentioning
confidence: 93%
“…The associations between genotypes and growth traits of cattle were analyzed using the statistical software SPSS (Version 22.0, International Business Machines (IBM) Corporation, New York, USA; Pan et al, 2013). The linear model was as follow: Y ij k = µ + A i + G j + e ij k , where Y ij k represents the observation of the body measurement traits, µ the overall mean of each trait, A i the fixed effect of age, G j the fixed effect of genotype or combined genotype, and e ij k the random residual error Zhang et al, 2015). The effect of genotype was a significant variation source, when the P value for the difference was less than 0.05 between the least squares means for each genotype Zhao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%